PENERAPAN METODE GROSS UP DALAM PENGHITUNGAN PAJAK PENGHASILAN PASAL 21 SEBAGAI SRATEGI PENGHEMATAN PAJAK PENGHASILAN BADAN PADA PT XYZ - Widjaja, P Helen; Yono, Ade (Jurnal Ekonomi, 2016)
This case study was conducted to see the implementation of tax planning for Income Tax Article 21 using 4 (four) alternative. Based on the analysis, implementation of gross-up method will provide greater tax savings compared with other alternative. Calculation of Income Tax Article 21 using gross-up method can result in increasing employees’ gross salary, and also which will affect the corporate profit decrease because the expense that can be deducted in the fiscal will be increase, so that the corporate income tax borne by the corporate is going down. On the other hand, gross-up method is advantageous because the employee will receive larger take home pay.